Strategi Guru dalam Meningkatkan Pembelajaran SKI Siswa - Mila Febrianty; Herman (Yayasan Ishlahul Muslimin Konawe Selatan, 2025)
This research was conducted to find out about the strategies applied by teachers in improving the learning of Islamic cultural history in grade VIII students at MTs Negeri 2 Kendari. This type of research is field research, with a qualitative descriptive approach, using data collection methods in the form of field observations, interviews, and documentation. As for the analysis, researchers use descriptive qualitative analysis which aims to describe completely and deeply about the phenomenon under study. The results showed that (1) The learning process of Islamic cultural history in class VIII began with preliminary activities, information delivery, tests, and follow-up activities. (2) Strategies applied by teachers in improving learning the history of Islamic culture using direct learning strategies, expository learning strategies, and inquiry learning strategies. Researchers found that the strategies applied by teachers in improving the learning of Islamic cultural history in students in grade VIII are direct learning strategies, expository learning strategies, and inquiry learning strategies applied by looking at the needs, characteristics, and cognitive abilities of students in different VIII grades.